Covid-19 and spirometry in this age - Angela Klain; Cristiana Indolfi; Giulio Dinardo; Fabio Decimo; Michele Miraglia Del Giudice (BMC, 2022)
Abstract In the last year, many countries adopted a plan to contain hospital infections by Sars-Cov-2 also limiting pulmonary function tests (PFTs), exclusively to indispensable cases. All the recommendations of the major scientific societies regarding the use of PFTs, in particular spirometry, in the Covid era were formulated in the initial period of the pandemic. Currently, the new scientific knowledge about Sars-Cov-2 and the vaccination among healthcare workers, shown new insight to start doing PFTs again to help the investigation and monitoring of patients with respiratory pathology. In this article, we sum up the recommendations of major International Respiratory Societies, and we shared our experience about PFTs in a Pediatric Respiratory Disease Unit during the pandemic.